Resilience of small-scale societies: a view from drylands. - Gomez-Baggethun, E.; Salpeteur, M.; Puy, A.; Biagetti, S.; Scheffran, J.; Balbo, A.L. (Resilience Alliance, 2016)
To gain insights on long-term social-ecological resilience, we examined adaptive responses of small-scale societies to dryland-related hazards in different regions and chronological periods, spanning from the mid-Holocene to the present. Based on evidence from Africa (Sahara and Sahel), Asia (south margin of the Thar desert), and Europe (South Spain), we discuss key traits and coping practices of small-scale societies that are potentially relevant for building resilience. The selected case studies illustrate four main coping mechanisms: mobility and migration, storage, commoning, and collective action driven by religious beliefs. Ultimately, the study of resilience in the context of drylands emphasizes the importance of adaptive traits and practices that are distinctive of small-scale societies: a strong social-ecological coupling, a solid body of traditional ecological knowledge, and a high degree of internal cohesion and self-organization.
Keywords: adaptation; climate change; coping mechanisms; drylands; resilience; social-ecological systems; sustainability; traditional ecological knowledge